Relationship between brief and prolonged repeated sprint ability - Oliver, J. L.; Armstrong, N.; Williams, C. A. (Journal of Science and Medicine in Sport, 2009)
Repeated sprint ability (RSA) is often assessed over a brief time period with limited recovery between sprints; however, it is not known how performance in such tests is related to the ability to perform repeated sprints over a more prolonged duration. Eighteen boys aged 15.3 ± 0.5 years completed both a brief and prolonged RSA test on a non-motorised treadmill. The brief RSA test consisted of seven 5 s sprints with 20 s of recovery between sprints and the prolonged RSA test lasted for 42 min and included a 5 s sprint every 2 min. There was a moderate but significant relationship between the mean speed in both tests (r = 0.51, p < 0.05). The maximal speed achieved in a single sprint provided strong relationships with both brief RSA speed (r >/= 0.72, p < 0.001) and prolonged RSA speed (r r >/= 0.77, p < 0.001). Total work done during the brief protocol was significantly correlated to both total work (r = 0.81, p < 0.001) and total sprint distance (r = 0.79, p < 0.001) during the prolonged test. There were no significant relationships between percentage decrement scores across the two protocols (r r >/= 0.33, p > 0.05). Maximal speed in a single sprint and total work done during repeated sprints represent general qualities related to RSA that are independent of the test protocol. The mean speed and decrements in performance represent specific RSA qualities, which are dependent on the frequency of sprints and duration of the test protocol.